2022
DOI: 10.1186/s13567-022-01104-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel C-type lectin from Trichinella spiralis mediates larval invasion of host intestinal epithelial cells

Abstract: The aim of this study was to investigate the characteristics of a novel type C lectin from Trichinella spiralis (TsCTL) and its role in larval invasion of intestinal epithelial cells (IECs). TsCTL has a carbohydrate recognition domain (CRD) of C-type lectin. The full-length TsCTL cDNA sequence was cloned and expressed in Escherichia coli BL21. The results of qPCR, Western blotting and immunofluorescence assays (IFAs) showed that TsCTL was a surface and secretory protein that was highly expressed at the T. spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that rTsCTL promoted the IIL larvae invasion into host’ IEC, but the mechanism of rTsCTL promotion on the IIL invasion was unclear [ 20 ]. The C-type lectin of Cryptosporidium parvum mediated the Cryptosporidium attachment and infection to IEC by interacting with heparan sulfate proteoglycans (HSPG) on the IEC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that rTsCTL promoted the IIL larvae invasion into host’ IEC, but the mechanism of rTsCTL promotion on the IIL invasion was unclear [ 20 ]. The C-type lectin of Cryptosporidium parvum mediated the Cryptosporidium attachment and infection to IEC by interacting with heparan sulfate proteoglycans (HSPG) on the IEC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant plasmid pQE-80L/TsCTL constructed in our laboratory was used as an amplification template [ 20 ]. The TsCTL gene was amplified by PCR using specific primers with BamHI and EcoRI restriction sites (in bold) as follows: 5′-C GGATCC AACCGTTTTCCGTGCCGTATCAAAT-3′ and 5′-GCGC GAATTC TCACTCCAACGAA TGACAAATTC-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble crude antigens of diverse T . spiralis stage worms (ML, IIL, AW and NBL) and their ES antigens were prepared as reported before [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…After washing with PBS three times, the cells were fixed with 4% paraformaldehyde for 20 min at room temperature, incubated with 20 µg/mL proteins (rTsDPP1, AW ESA and TRX tag protein) at 37 °C for 2 h, blocked with 5% goat serum at 37 °C for 1 h, and then incubated with 1:10 dilutions of different serum (anti-rTsDPP1 serum, infection serum and preimmune serum) at 37 °C for 1 h. Alexa Fluor 488-conjugated anti-mouse IgG (1:100; Abways, Shanghai, China) served as the secondary antibody, and 4′,6-diamidino-2-phenylindole (DAPI) was used to dye the cell nucleus. The fluorescence signal was observed under fluorescence and confocal microscopy (Olympus, Tokyo, Japan) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%